MESSAGE DESIGN LOGIC AND THE RECONSTRUCTION OF BUGIS-MAKASSAR CULTURAL BRAND IMAGE ON INSTAGRAM (International Journal of Cultural and Social Science, 2026)
This study analyzes Message Design Logic (MDL) in reconstructing the brand image of Kaeel Baju Bodo on Instagram. It aims to identify expressive, conventional, and rhetorical design logic in shaping a Bugis-Makassar cultural brand identity. A qualitative case study was conducted on the Instagram account @kaeel.bajubodo. Data were collected through observation, interviews, and documentation involving 30 informants and analyzed using the Miles, Huberman, and Saldaña model with NVivo support. Findings show expressive design logic dominates through aesthetic visuals and spontaneous communication that enhance audience attention and brand awareness. Conventional logic appears in service information and procedures, while rhetorical logic constructs cultural meaning through storytelling. However, integration among the three logics remains inconsistent. The novelty lies in applying MDL to examine cultural brand reconstruction on Instagram as digital cultural branding. The study concludes that brand image is shaped by visual, informational, and symbolic elements that are not yet fully integrated.